Solving math and science problems in the real world with a computational mind - Juan Carlos Olabe; Xabier Basogain; Miguel Ángel Olabe; Inmaculada Maíz; Carlos Castaño (Springer, 2014)
This article presents a new paradigm for the study of Math and Sciences curriculum during primary and secondary education. A workshop for Education undergraduates at four different campuses (n=242) was designed to introduce participants to the new paradigm. In order to make a qualitative analysis of the current school methodologies in mathematics, participants were introduced to a taxonomic tool for the description of K-12 Math problems. The tool allows the identification, decomposition and description of Type-A problems, the characteristic ones in the traditional curriculum, and of Type-B problems in the new paradigm. The workshops culminated with a set of surveys where participants were asked to assess both the current and the new proposed paradigms. The surveys in this study revealed that according to the majority of participants: (i) The K-12 Mathematics curricula are designed to teach students exclusively the resolution of Type-A problems; (ii) real life Math problems respond to a paradigm of Type-B problems; and (iii) the current Math curriculum should be modified to include this new paradigm.